Новые находки Cobitis aurata (Piaces, Cobitidae) в водоемах Украины - Мовчан, Ю.В. (Вестник зоологии, 1982)
Cobilis aurata (F i l i p p i) is first reported from the Seversky Donets and Trubezh rivers (Dniper basin). Thesample is identified as ssp. balanica Karaman.